Incoming Extradition in Indonesia and Its Implication to Human Rights - Efendi Lod Simanjuntak (Walisongo Law Review (Walrev), 2019)
Law enforcement to transnational fugitives especially those perpetrators of money laundering with international dimension in Indonesia, in particular related to incoming extradition is needed to reconstruct. This is because hitherto, the decision to extradite is the decision of the executive branch as stipulated in Act No.1 of 1979 on Extradition. Hence, the consideration for the government to extradite is more on political concern rather than judicial. This practice is deemed neglecting the protection of human rights and creating legal uncertainty, especially in relation to detention period that could exceed beyond admissible time as stipulated in KUHAP because of the grace period on the issuance of the Presidential Decision. This research is doctrinal and field study. Based on findings in the field, incoming extradition request must be based on the court’s decision, or judicial order in the future to ensure protection of human rights and legal certainty of the person who is subject of the extradition and to the requested country. Penegakan hukum terhadap buronan transnasional, terutama para pelaku pencucian uang di Indonesia, perlu sebuah rekontruksi khususnya terkait dengan ekstradisi. Ini karena sampai sekarang, keputusan untuk mengekstradisi adalah keputusan cabang eksekutif sebagaimana diatur dalam Undang-Undang No.1 tahun 1979 tentang Ekstradisi. Oleh karena itu, pertimbangan bagi pemerintah untuk mengekstradisi lebih pada masalah politik daripada peradilan. Praktik ini dianggap mengabaikan perlindungan hak asasi manusia dan menciptakan ketidakpastian hukum, terutama dalam kaitannya dengan masa penahanan yang dapat melebihi melampaui waktu yang dapat diterima sebagaimana diatur dalam KUHAP karena masa tenggang pada penerbitan Keputusan Presiden. Penelitian ini bersifat doktrinal dan studi lapangan. Berdasarkan temuan di lapangan, permintaan ekstradisi yang masuk harus didasarkan pada keputusan pengadilan, atau perintah pengadilan di masa depan untuk memastikan perlindungan hak asasi manusia dan kepastian hukum dari orang yang menjadi sasaran ekstradisi dan ke negara yang diminta.